Odpowiedź :
Odpowiedź:
a) A+B+C = 5a + 7y - 3 - 9a - 5y + 8 + 4a - 2y - 4 = 1
b) B-C+D = - 9a - 5y + 8 - 4a + 2y + 4 - 3y + 8a - 2 = - 5a - 6y + 10
c) -D-B+A = 3y - 8a + 2 + 9a + 5y - 8 + 5a + 7y - 3 = 15y + 6a - 9 = 3(5y + 2a - 3)
d) B-A+C-D = - 9a - 5y + 8 - 5a - 7y + 3 + 4a - 2y - 4 + 3y - 8a + 2 = -18 a -10y +9
Szczegółowe wyjaśnienie:
Odpowiedź:
Szczegółowe wyjaśnienie:
(5a+7y-3)+ (-9a -5y+8)+ (4a-2y-4)=
=5a+7y-3-9a-5y+8+4a-2y-4=
=1
(-9a -5y+8) -(4a-2y-4)+ (-3y+8a-2)=
=-9a-5y+8-4a+2y+4 -3y+8a-2=
= -5a -6y+10
-(-3y+8a-2) -(-9a -5y+8)+ (5a+7y-3)=
=3y-8a+2+9a+5y-8+5a+7y-3=
=6a+15y-9
(-9a -5y+8) - (5a+7y-3)+ (4a-2y-4) -(-3y+8a-2)=
=-9a -5y+8-5a-7y+3+4a-2y-4+3y-8a+2=
= -18a-11y+9